Connections in towers for wind converters, part I: Evaluation of down-scaled experiments. (December 2015) - Pavlović, Marko; Heistermann, Christine; Veljković, Milan; Pak, Daniel; Feldmann, Markus; Rebelo, Carlos; da Silva, Luis Simões
Abstract: The cost of a tubular steel tower supporting a wind converter becomes increasingly important in a competitive energy market. In-situ connection between tower segments is an important factor of the design. The tower segments are usually connected by welded ring flanges. An alternative solution based on a novel single lap friction connection is analysed. The purpose of the research presented in this paper is to thoroughly analyse the behaviour of both connections by an experimental testing programme and advanced finite element analysis (FEA). Down-scaled experiments of ring flange and friction connection in circular towers were performed using a 4-point bending test set-up. Altogether eight connections joining cylindrical shell, 1 m diameter, plate thickness 8 mm and total span of about 7 m were tested. A friction connection with long open slotted holes and two different cases of the ring flange connection are considered: with perfectly flat flanges and flanges with geometric imperfection. Results of advanced quasi-static FEA, using explicit dynamic solver and ductile damage material model for bolts, are compared to experiments. Failure modes, bolt forces and distribution of meridional membrane stresses in the shell in the vicinity of connections are analysed. Existing hand-calculation models, for the bolt force and normal stress distribution in the shell are validated by experiments and FEA. Graphical abstract: Highlights: Advanced FEA of ring flange and friction connection in a steel tubular tower. Evaluation of hand-calculation methods by FEA and experiments. Influence of out of flatness ring flange imperfection on fatigue endurance. Loss of preloading force in bolts of a friction connection. Advantages of friction connection compared to ring flange connection.